Industry 4.0 Readiness - DBS Bank Singapore Case Study - Soeung, Hong; Kašparová, Eva, 1958-; Martínez, Felipe; Vysoká škola ekonomická v Praze. Podnikohospodářská fakulta (2020)
The thesis will focus on the concept of the Industry 4.0, the importance of human capital and competencies in corporation to become ready for the industrial revolution.Methodology will be based on secondary data analysis on annual reports, published statistics and other sources, along with a case study of a well-renowned company (DBS Bank Singapore), which successfully transformed to a smart company.
Vedoucí práce: Eva Kašparová
Bakalářská práce (Bc.)—Vysoká škola ekonomická v Praze. Fakulta podnikohospodářská, 2020
Obsahuje bibliografii
Textový (vysokoškolská kvalifikační práce)
Rok obhajoby 2020
Způsob přístupu: Internet
Keywords: business administration/corporate finance and management [obor bakal. práce]; bakalářské práce; bachelor's theses